2022
DOI: 10.2147/ijgm.s329942
|View full text |Cite
|
Sign up to set email alerts
|

Body Dysmorphic Disorder Symptoms: Prevalence and Risk Factors in an Arab Middle Eastern Population

Abstract: Background The present study examined the prevalence of and risk factors for symptoms of body dysmorphic disorder (BDD) in the general population of Jeddah, a large port city in Saudi Arabia. Methods This cross-sectional study surveyed a convenience sample of 520 adults. We used a validated self-screening measure to assess BDD, the body dysmorphic disorder questionnaire (BDDQ). Results The prevalence of significant BDD symptoms among the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
4
11
1
Order By: Relevance
“…Different BDD screening instruments may produce different results [15]. In Saudi Arabia, multiple studies were conducted to assess the prevalence of BDD; the reported prevalence of BDD among the general population is between 4.2% and 8.8% and 4.4-12.3% among female students [6][7][8][9]. A study done in the AL-Qassim region of Saudi Arabia on dermatology patients shows that the prevalence of BDD is 18.6% [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different BDD screening instruments may produce different results [15]. In Saudi Arabia, multiple studies were conducted to assess the prevalence of BDD; the reported prevalence of BDD among the general population is between 4.2% and 8.8% and 4.4-12.3% among female students [6][7][8][9]. A study done in the AL-Qassim region of Saudi Arabia on dermatology patients shows that the prevalence of BDD is 18.6% [16].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review conducted in 2016 showed that the estimated prevalence of BDD in the general population is around 1.9-2.2% [5]. Locally in Saudi Arabia, the reported prevalence of BDD among the general population is around 4.2-8.8%, and among female students is 4.4-12.3% [6][7][8][9]. Since there is no available up-to-date data concerning the BDD prevalence in Makkah City, Saudi Arabia, to address this, the current study explores the prevalence of body dysmorphic disorder among the general population in Makkah City, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 The estimated prevalence for the general population diagnosed with BDD ranges from 2.4% to 8.8%. 4,5 Although BDD affects both genders, several studies indicate that it is more common among females. 6 BDD may have a higher prevalence in cosmetic settings ranging from 9.2% to 11.3% among patients seeking dermatological treatments and from 3% to 53% among those undergoing cosmetic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Based on a Literature review, risk factors including genetic, neurobiological, and environmental factors, childhood maltreatment, and comorbid psychiatric disorders were identified. 5 BDD was linked to a higher risk of comorbid anxiety and depressive disorders. 2 Additionally, childhood maltreatment and certain personality traits, such as perfectionism and neuroticism, were linked with an elevated risk of BDD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation